Effect of the Wetting Agent Sodium Lauryl Sulfate on the Pharmacokinetics of Alectinib: Results From a Bioequivalence Study in Healthy Subjects. Issue 3 (3rd October 2016) - Morcos, Peter N.; Parrott, Neil; Banken, Ludger; Timpe, Carsten; Lindenberg, Marc; Guerini, Elena; Dall, Georgina; Bogman, Katrijn; Sturm, Carolina; Zeaiter, Ali; Martin‐Facklam, Meret; Phipps, Alex
Abstract: The anaplastic lymphoma kinase (ALK) inhibitor alectinib is an effective treatment for ALK ‐positive non‐small‐cell lung cancer. This bioequivalence study evaluated the in vivo performance of test 3 formulations with the reduced wetting agent sodium lauryl sulfate (SLS) content. This randomized, 4‐period, 4‐sequence, crossover study compared alectinib (600 mg) as 25%, 12.5%, and 3% SLS hard capsule formulations with the reference 50% SLS clinical formulation in healthy subjects under fasted conditions (n = 49), and following a high‐fat meal (n = 48). Geometric mean ratios and 90% confidence intervals (CIs) for Cmax, AUC0–last, and AUC0–∞ of alectinib, its major active metabolite, M4, and alectinib plus M4 were determined for the test formulations versus the reference formulation. Bioequivalence was concluded if the 90%CIs were within the 80% to 125% boundaries. The 25% SLS formulation demonstrated bioequivalence to the reference 50% SLS formulation for Cmax, AUC0–last, and AUC0–∞ of alectinib, M4, and alectinib plus M4 under both fasted and fed conditions. Further reductions in SLS content (12.5% and 3% SLS) did not meet the bioequivalence criteria. Cross‐group comparisons showed an approximately 3‐fold positive food effect. Reducing SLS to 25% resulted in a formulation that is bioequivalent to the current 50% SLS formulation used in alectinib pivotal trials.